Analisis Manajemen Risiko pada Usaha Bakso Mas Riyanto - Hakiki, Angga (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the risk management implemented by Bakso Mas Riyanto, a culinary business located on Jalan Manisi, Cibiru, Bandung City. In small businesses like this, risk management is crucial to ensure operational continuity despite facing various challenges. The research uses a qualitative approach with direct analysis methods through observation, semi-structured interviews, and documentation. The findings show that the risks faced by Bakso Mas Riyanto can be categorized into three main groups: operational risks, financial risks, and external risks. Several strategies implemented to manage these risks include equipment maintenance, raw material management, and innovations such as home delivery services. However, challenges remain, such as reliance on single suppliers and manual financial recording. This study suggests that small business owners should utilize simple technologies to support financial management and expand cooperation networks with related parties to reduce risks. Effective risk management will enable small businesses to survive and thrive amid increasingly intense competition.